2020
DOI: 10.1016/j.resourpol.2020.101838
|View full text |Cite
|
Sign up to set email alerts
|

Is the relationship between oil-gas prices index and economic growth in Turkey permanent?

Abstract: Oil and gas are the most important inputs that countries use in their production process. For this reason, changes in oil-gas prices affect economic growth, which is the most important macroeconomic performance indicator. This study aims to investigate whether the relations between the oil-gas prices index and economic growth are permanent in Turkey, covering the period 1998Q1-2019Q4. For this purpose, the relationships between variables are first examined by Granger and Toda-Yamamoto causality tests with stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…To carry out the Toda-Yamamoto test with a structural break, we formed the following Equation (1) which is based on Vector Autoregressive Models (VAR) developed by Sims (1980) and the Toda & Yamamoto's (1995) causality test. Since there is a strong deterministic trend especially in lhinf, we added a deterministic trend as well as dummy variables representing the structural breaks in variables to the classical Toda & Yamamoto (1995) causality test equation, as was done in Kırca et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…To carry out the Toda-Yamamoto test with a structural break, we formed the following Equation (1) which is based on Vector Autoregressive Models (VAR) developed by Sims (1980) and the Toda & Yamamoto's (1995) causality test. Since there is a strong deterministic trend especially in lhinf, we added a deterministic trend as well as dummy variables representing the structural breaks in variables to the classical Toda & Yamamoto (1995) causality test equation, as was done in Kırca et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Kırca et al (2020) conducted a study in Turkey to explore whether a fall in oil price affects the economic growth of the country and found that due to dependence on exported energy products, any change in the price of oil affects the economy significantly [17]. They suggest that the recent fall in oil price due to COVID-19 affected the Turkish economy positively.…”
Section: Impact Of Oil Prices On Economic Growthmentioning
confidence: 99%
“…Examples of studies examining the relationships between crude oil prices and different macroeconomic factors are papers by Kırca et al [15], Aye and Odhiambo [16] or Zakaria et al [17]. Kırca et al [15] investigated the relationship between the oil-gas prices index and economic growth in Turkey in the period 1998-2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Examples of studies examining the relationships between crude oil prices and different macroeconomic factors are papers by Kırca et al [15], Aye and Odhiambo [16] or Zakaria et al [17]. Kırca et al [15] investigated the relationship between the oil-gas prices index and economic growth in Turkey in the period 1998-2019. The results, based on Granger and the Frequency Domain Causality tests, demonstrated an insignificant causality relationship between the variables, whereas the Toda-Yamamoto causality test with a structural break exhibited a causal relation running from oil-gas to economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%